A Quasi-Experimental Study of Project-Based Learning's Influence on Critical Thinking Skills Among Moroccan EFL Undergraduates - Imad Hamdanat; Lamiae Azzouzi; Brahim El Kouar; Abderrazak Zaafour; Nadif Bendaoud; Anouar Mohamed El Kasri; Abdelaziz Ouchaib; Ouadiha El Jemli (Yayasan Visi Intan Permata, 2025)
This research examined the effects of Project-Based Learning (PBL) on the development of critical thinking skills among undergraduate students in the English studies program at the Faculty of Arts and Humanities in Meknes during a 12-week intervention. A quasi-experimental design compared a PBL group to a traditional instruction control group. Critical thinking was assessed via pre- and post-tests and interviews. The independent samples t-tests showed no significant differences between groups in the pre-test; however, the PBL group demonstrated significant advantages in the post-test (t(59.619) = -13.353, p < .001). Paired samples t-tests confirmed within-group improvements for the PBL group. ANCOVA, controlling for pre-test scores, reinforced the significant positive effect of PBL on critical thinking. Semi-structured interviews were also conducted to back up the quantitative data. These results highlight PBL as an effective teaching method for developing critical thinking skills among undergraduate students in English studies. The study contributes to the growing body of evidence supporting PBL’s efficacy in enhancing higher-order cognitive abilities.